Applications of optical coherence tomography angiography in glaucoma: current status and future directions - Shen, Ruyue; Chan, Leo Ka Yu; Yip, Amber Cheuk Wing; Chan, Poemen P. (Frontiers in Medicine, 2024)
Glaucoma is a leading cause of irreversible blindness worldwide, with its pathophysiology remaining inadequately understood. Among the various proposed theories, the vascular theory, suggesting a crucial role of retinal vasculature deterioration in glaucoma onset and progression, has gained significant attention. Traditional imaging techniques, such as fundus fluorescein angiography, are limited by their invasive nature, time consumption, and qualitative output, which restrict their efficacy in detailed retinal vessel examination. Optical coherence tomography angiography (OCTA) emerges as a revolutionary imaging modality, offering non-invasive, detailed visualization of the retinal and optic nerve head microvasculature, thereby marking a significant advancement in glaucoma diagnostics and management. Since its introduction, OCTA has been extensively utilized for retinal vasculature imaging, underscoring its potential to enhance our understanding of glaucoma's pathophysiology, improving diagnosis, and monitoring disease progression. This review aims to summarize the current knowledge regarding the role of OCTA in glaucoma, particularly its potential applications in diagnosing, monitoring, and understanding the pathophysiology of the disease. Parameters pertinent to glaucoma will be elucidated to illustrate the utility of OCTA as a tool to guide glaucoma management.